Spin‐Lasing in Bimodal Quantum Dot Micropillar Cavities. Issue 4 (1st February 2022) - Heermeier, Niels; Heuser, Tobias; Große, Jan; Jung, Natalie; Kaganskiy, Arsenty; Lindemann, Markus; Gerhardt, Nils C.; Hofmann, Martin R.; Reitzenstein, Stephan
Abstract: Spin‐controlled lasers are highly interesting photonic devices and have been shown to provide ultrafast polarization dynamics in excess of 200 GHz. In contrast to conventional semiconductor lasers their temporal properties are not limited by the intensity dynamics, but are governed primarily by the interaction of the spin dynamics with the birefringent mode splitting that determines the polarization oscillation frequency. Another class of modern semiconductor lasers are high‐ β emitters, which benefit from enhanced light–matter interaction due to strong mode confinement in low‐mode‐volume microcavities. In such structures, the emission properties can be tailored by the resonator geometry to realize for instance bimodal emission behavior in slightly elliptical micropillar cavities. This attractive feature is utilized to demonstrate and explore spin‐lasing effects in bimodal high‐ β quantum dot micropillar lasers. The studied microlasers with a β ‐factor of 4% show spin‐laser effects with experimental polarization oscillation frequencies up to 15 GHz and predicted frequencies up to about 100 GHz, which are controlled by the ellipticity of the resonator. These results reveal appealing prospects for very compact, ultrafast, and energy‐efficient spin‐lasers and can pave the way for future purely electrically injected spin‐lasers enabled by short injection path lengths. Abstract : Spin‐lasing in cavity enhanced high‐ β microlasers promises high energy efficiency and ultrahigh bitrate optical data communication. Here, bimodal quantum dot micropillars show spin‐laser effects with polarization oscillation frequencies up to 15 GHz controlled by the ellipticity of the resonator. These nanophotonic structures have appealing prospects for compact spin‐lasers and can pave the way for future purely electrically injected devices.